The impact of viral dynamics on the clinical severity of infants with respiratory syncytial virus bronchiolitis. Issue 8 (23rd April 2015) - Zhou, Lili; Xiao, Qiuyan; Zhao, Yao; Huang, Ailong; Ren, Luo; Liu, Enmei
<x xml:space="preserve">Abstract</x> The impact of dynamic respiratory syncytial virus (RSV) load on the clinical severity of hospitalized infants with bronchiolitis has not been clarified. Nasopharyngeal aspirates were obtained from 60 infants who were diagnosed with bronchiolitis within 96 hr of wheezing onset upon admission and on days 3, 5, and 7 in the hospital, and 17 respiratory viruses were detected. The RSV load was quantified by real‐time qPCR for RSV subtypes A and B at different time points. Scoring criteria were used to evaluate the degree of severity. A total of 40 infants were determined to be RSV‐positive, nine were identified as RSV subtype A (RSVA), and 31 were RSV subtype B (RSVB). The peak RSV load was observed upon admission, and the RSV load decreased significantly over time; in addition, this decrease began to have significant differences on day 5. There was a positive correlation between the RSV load and the clinical score (r2 = 0.121 and P < 0.001). According to the clinical scores, the infants in the severe group tended to have higher RSV loads than those in the moderate and mild groups. Multivariate logistic regression models revealed that the viral load on day 3 was independently associated with the degree of severity. This study elucidated that a higher mean RSV load was associated with a more severe disease and a longer duration of hospitalization and symptoms. This study also clarified RSV replication in infants and provides a theoretical basis for specifying an anti‐RSV therapy strategy. J. Med. Virol. 87:1276–1284, 2015. © 2015 Wiley Periodicals, Inc.